Prevalence of human visceral leishmaniasis in Iran: A systematic review and meta-analysis. (April 2021) - Rostamian, Mosayeb; Bashiri, Homayoon; Yousefinejad, Vahid; Bozorgomid, Arezoo; Sohrabi, Nasrollah; Raeghi, Saber; Khodayari, Mohammad Taghi; Ghadiri, Keyghobad; Rezaeian, Shahab
Highlights: To the best of our knowledge, this is the ﬁrst systematic review of the prevalence of HVL in Iran. This study found that the pooled prevalence of HVL infection was low in Iran. According to the results, the prevalence of HVL infection has decreased in Iran over the last two decades. In this study, the highest prevalence of HVL was found in the northern (3%, 95 % CI: 1–5%) and southern (2.1 %, 95 % CI: 1.4–2.8 %) areas of Iran. However, despite the efforts made by Iranian public health authorities for controlling and preventing HVL, not only new human cases of VL continue to occur in old endemic foci, but also the disease has been reported in new areas where it was non-endemic previously. In this regard, appropriate measures should be taken to control VL and prevent its spread to other areas. Abstract: Leishmania infantum is the main cause of human visceral leishmaniasis (HVL; also known as kala-azar) in the Middle East and may be fatal if left untreated. This disease was ﬁrst reported in 1949 in Iran. Despite marked improvements in hygiene and sanitation conditions, the disease is still endemic in some parts of Iran. It is difficult to determine the current prevalence of HVL in Iran due to the scarcity of comprehensive studies in this regard. In response to this gap, a systematic review and meta-analysis was conducted to gain better understanding of HVL epidemiology in the general population of Iran. English and Persian databases were searched for studies reporting the prevalence and risk factors associated with HVL in the Iranian people from January 1995 to December 2019. The reported data were selected according to inclusion and exclusion criteria. The pooled prevalence of HVL infection and its 95 % confidence intervals were calculated. Quality assessment, heterogeneity testing and publication bias assessment were also done. Literature search revealed 3634 studies, of which 35 studies met our eligibility criteria, with a total of 50, 716 individuals. The meta-analysis was performed on 31 out of 35 included studies. The estimated pooled prevalence of HVL infection according to seropositivity was 2% (95 % CI: 1–2%) in the general population of Iran in which western and northern provinces had the lowest and the highest prevalence, 0.5 % (95 %CI, 0.2−0.7%) and 3% (95 %CI, 1–5 %), respectively. The seroprevalence of HVL among females (2%; 95 %CI, 1–2 %) was more than males (1%; 95 %CI, 1–2 %). The ≤10 and >10 years age groups had similar seroprevalence rates (1%, 95 %CI, 1–2 % versus 1%, 95 %CI, 0–1 %, respectively). There was no signiﬁcant difference in terms of geographic area, age and sex. Of 31 studies included in the meta-analysis, the most common diagnostic test was the direct agglutination test (96.77 %). To the best of our knowledge, this is the ﬁrst systematic review of the prevalence of HVL in Iran. The results showed a low seroprevalence of HVL infection. However, the lack of published reports of HVL in an area does not exclusively mean the absence of the disease or carrier. We therefore recommend further studies in this regard.